Monitoring of electrical activity of the diaphragm shows failure of T-piece trial earlier than protocol-based parameters in prolonged weaning in non-communicative neurological patients - Trapp, Oliver; Fiedler-Kalenka, Mascha; Kalenka, Armin (Neurocritical care, 2017)
Background: The weaning target in tracheotomised patients is not extubation, but spontaneous breathing without the support of a ventilator. Overloading the respiratory pump during such spontaneous breathing trials is unfavorable, prolongs weaning time, and increases morbidity and mortality. The goal of this study was to evaluate the electrical activity of the diaphragm during a t-piece trial in non-communicative neurological patients and the comparison to clinical parameters of exhaustion. Methods: During multiple t-piece trials, the electrical activity of the diaphragm was obtained before, during and after the end of the trial. T-piece trials were grouped based on the reason for stopping the trial (exhaustion or allotted time period). Results: Twenty-nine tracheotomised patients in prolonged weaning (29 ± 22 days ventilated at the start of the study) were included in a prospective observational study. T-piece trials (n = 152; 5 ± 2 per patient) were grouped based on the reason for stopping the trial (n = 91 because of exhaustion; n = 61 because of the allotted time period). We found that the electrical activity of the diaphragm exhibits an earlier increase than protocol-based clinical parameters in patients who failed the trial due to exhaustion. The electrical activity of the diaphragm shows no relevant difference during the t-piece trial in patients in whom the trial was stopped due to the allotted time period per protocol. Conclusions: Monitoring the electrical activity of the diaphragm in non-communicative neurological patients in prolonged weaning allows earlier detection of exhaustion than protocol-based parameters.